Promoción turística para el desarrollo del turismo sostenible en el cantón El Empalme, año 2020 - Alava Naranjo, Fabián Orlando (2021)
This project is developed in the canton El Empalme which is known for its cultural richness, being located in a strategic point to be visited by national and foreign tourists due to its native beauty where its natural landscapes, pleasant climate, gastronomy, art, stand out. friendly people turning El Empalme into an investment potential to promote tourism so that they can be enjoyed by themselves and strangers. The applied techniques and methods determined that despite the fact that in the El Empalme canton there is a tourist potential in art, culture, native traditions of the Montuvian people, natural landscapes this has not had a greater impulse to promote tourism that can be carried out in the canton, leaving one of the sectors that currently generates a large number of economic resources, and that also reactivates commerce through micro-entrepreneurship, improving the quality of life of its inhabitants. It is appropriate that an organizational, planned, and directed proposal be made to the tourist promotion of the canton by selecting the means of dissemination for the promotion of tourism, as well as the places, culture, gastronomy, nature to capture the attention of the tourist